Long-Term Elevated Inflammatory Protein Levels in Asymptomatic SARS-CoV-2 Infected Individuals - Tserel, Liina; Jõgi, Piia; Naaber, Paul; Maslovskaja, Julia; Häling, Annika; Salumets, Ahto; Zusinaite, Eva; Soeorg, Hiie; Lättekivi, Freddy; Ingerainen, Diana; Soots, Mari; Toompere, Karolin; et al. (Frontiers in Immunology, 2021)
The clinical features of SARS-CoV-2 infection range from asymptomatic to severe disease with life-threatening complications. Understanding the persistence of immune responses in asymptomatic individuals merit special attention because of their importance in controlling the spread of the infections. We here studied the antibody and T cell responses, and a wide range of inflammation markers, in 56 SARS-CoV-2 antibody-positive individuals, identified by a population screen after the first wave of SARS-CoV-2 infection. These, mostly asymptomatic individuals, were reanalyzed 7-8 months after their infection together with 115 age-matched seronegative controls. We found that 7-8 months after the infection their antibodies to SARS-CoV-2 Nucleocapsid (N) protein declined whereas we found no decrease in the antibodies to Spike receptor-binding domain (S-RBD) when compared to the findings at seropositivity identification. In contrast to antibodies to N protein, the antibodies to S-RBD correlated with the viral neutralization capacity and with CD4+ T cell responses as measured by antigen-specific upregulation of CD137 and CD69 markers. Unexpectedly we found the asymptomatic antibody-positive individuals to have increased serum levels of S100A12, TGF-alpha, IL18, and OSM, the markers of activated macrophages-monocytes, suggesting long-term persistent inflammatory effect associated with the viral infection in asymptomatic individuals. Our results support the evidence for the long-term persistence of the inflammation process and the need for post-infection clinical monitoring of SARS-CoV-2 infected asymptomatic individuals.